2006
DOI: 10.1098/rspb.2006.3586
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of the antiherbivore effects of silica in grasses: impacts on foliage digestibility and vole growth rates

Abstract: The impact of plant-based factors on the population dynamics of mammalian herbivores has been the subject of much debate in ecology, but the role of antiherbivore defences in grasses has received relatively little attention. Silica has been proposed as the primary defence in grasses and is thought to lead to increased abrasiveness of foliage so deterring feeding, as well as reducing foliage digestibility and herbivore performance. However, at present there is little direct experimental evidence to support thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
191
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(198 citation statements)
references
References 44 publications
(65 reference statements)
5
191
0
2
Order By: Relevance
“…Massey and Hartley (2006) demonstrated that silica in grasses not only deterred feeding by field voles, but also inhibited the growth rates of the voles by decreasing nitrogen absorption from foliage. Ma et al (2006), working with rice, identified for the first time in a higher plant a silicon transporter gene, called Lsil, that controls silica uptake.…”
Section: Why Plants Make Phytolithsmentioning
confidence: 99%
“…Massey and Hartley (2006) demonstrated that silica in grasses not only deterred feeding by field voles, but also inhibited the growth rates of the voles by decreasing nitrogen absorption from foliage. Ma et al (2006), working with rice, identified for the first time in a higher plant a silicon transporter gene, called Lsil, that controls silica uptake.…”
Section: Why Plants Make Phytolithsmentioning
confidence: 99%
“…Plants respond to grazing intensity of the previous year by adjusting the Si content (by 0.6-1 percentage point; Wieczorek et al, 2015b) in their leaves (see also Massey et al, 2008;Reynolds et al, 2012), and voles are in turn negatively affected by increased phytolith levels (Massey and Hartley, 2006;Massey et al, 2008). But how plant phytoliths affect voles is still unclear.…”
Section: Variation Across Population Phasesmentioning
confidence: 99%
“…It has been shown that grazing induces an increased concentration of silicon (Si) in leaves Massey et al, 2007a;McNaughton and Tarrants, 1983;McNaughton et al, 1985;Reynolds et al, 2012), which reduces palatability and digestibility (Gali-Muhtasib et al, 1992;Massey et al, 2007b), and in turn lowers body mass and growth rate of voles (Massey and Hartley, 2006;Massey et al, 2008). Very recently, Wieczorek et al (2015b) demonstrated in the first field-based study that (1) silicon concentrations in leaves are determined by the vole population density, and thus by the grazing intensity, of the previous year, and (2) overwintering success in voles is correlated with leaf silicon levels in autumn.…”
Section: Introductionmentioning
confidence: 99%
“…High Al and/or Fe concentration in the water not only caused toxicity to rice, but also reduced the availability of P [33]. The low available P in the acid sulfate soil could be somewhat alleviated by the PSB, which were able increase soil pH to a level above 5 [8].…”
Section: Effects Of Applying Bio-fertilizer On Soilmentioning
confidence: 99%